종편TV 예능방송프로그램의 편성특성이 시청의도에 미치는 영향 - 이규환(Kyu-Hwan Lee) (한국콘텐츠학회 논문지, 17(6), 2017)
This study analyzed the impacts of programming characteristics perceived by the consumers of entertainment programs on general programming channels on watching intention and the data of a survey with 360 adult viewers in the capital area. Research questions were verified as follows: First, as a result of multiple regression to analyze the impacts of the factors of programming characteristics perceived by the consumers on their watching intention, setting personal characteristics as a control variable, programming characteristics as an independent variable and watching intention as a dependent variable, the regression model was significant. Thus, the more positive the perceived factors of programming characteristics, the more significant their watching intention improved. Second, the factors of programming characteristics significantly affecting watching intention had greater positive(+) impacts in the following order: Adjacency > substantiality > weight of genre > social evidence > relative advantage > ease of access. 본 연구에서는 종편TV 예능방송프로그램을 중심으로, 수용자가 지각하는 편성특성이 시청의도에 어떠한 영향을 미치는지 시청자 360명의 설문자료를 통해 분석하였다. 본 연구의 연구문제 검증결과를 정리하면 다음과 같다. 종편TV 예능방송프로그램 수용자가 지각하는 편성특성 요인이 시청의도에 미치는 영향을 분석하기 위하여, 개인적 특성을 통제변수로 투입하고, 편성특성을 독립변수로, 시청의도를 종속변수로 설정하여 다중회귀분석을 실시한 결과, 회귀모형이 유의한 것으로 나타났으며, 종편TV 예능방송프로그램 수용자가 지각하는 편성특성 요인이 긍정적일수록 시청의도가 유의하게 향상되는 것으로 볼 수 있다. 또한, 시청의도에 유의한 영향을 미치는 편성특성 요인은 인접성 > 내용적충실성 > 장르비중 > 사회적증거 > 상대적우위 > 접근용이성의 순으로 정(+)의 영향력을 나타내고 있었다. 결국 본 연구는 편성특성이 시청행위에 미치는 효과에 관해 경험적으로 검증하고, 종편 시청행위에 영향을 미치는 편성의 구조적 요인 내에서도 어떠한 우선순위가 있는지 밝혔다는데 의의가 있으며, 본 연구의 결과는 종편채널이 다양한 장르를 제작하고 편성하며, 이 과정에서 방송의 질적 수준과 지속성 및 차별성을 담보할 수 있는 전략이 필요함을 시사한다.